Sintesis Wahyu dan Akal: Dialektika Filsafat Ibnu Rusyd sebagai Model Pembelajaran Pendidikan Islam Modern - Priska Nurullah Sa’ada; Restu Fauzi; Nabila Khairunnisa; Syamsul Arifin (Civiliza Publishing, Indonesia., 2026)
Modern Islamic education faces increasingly complex challenges amid the developments of globalization, the digital revolution, and rapid social change. One of the fundamental issues that still persists is the dichotomy between religious knowledge and rational knowledge, which results in a learning process that tends to be normative and textual, and fails to foster the development of students’ critical thinking. This situation leads to weak reflective and dialogical abilities in understanding the realities of modern life. In this context, Ibn Rushd’s thought offers an integrative paradigm through the synthesis of revelation and reason as the epistemological foundation for a more humanistic and rational Islamic education. This article aims to analyze the dialectics of Ibn Rushd’s philosophy as a model for modern Islamic education that is relevant to the educational needs of the 21st century. This study employs a qualitative approach using library research methods through the analysis of various scholarly works related to the philosophy of Islamic education, the integration of knowledge, and the thought of Ibn Rushd. The results indicate that the concepts of burhani, jadali, and khitabi developed by Ibn Rushd have strong relevance to modern learning approaches such as critical thinking, problem-based learning, and collaborative learning. Furthermore, the synthesis of revelation and reason in Ibn Rushd’s thought can serve as an epistemological solution to the problem of the dichotomy of knowledge and religious radicalism.